Distinct PlzC mechanisms integrate chemotaxis and c-di-GMP signaling to regulate Vibrio cholerae motility and biofilm formation - Jin Hwan Park; Emily N. Kennedy; Sarvind Tripathi; Avery B. Romp; Seth M. Rubin; Robert B. Bourret; Fitnat H. Yildiz (Proceedings of the National Academy of Sciences, 2026)
Bacterial motility and biofilm formation are essential for the adaptation and survival of Vibrio cholerae , the causative agent of cholera. In many bacterial species, the second messenger c-di-GMP regulates these processes through PilZ domain proteins, however the downstream mechanisms have remained poorly defined. Here, we identify the PilZ domain protein PlzC as a key positive regulator of motility and biofilm formation through distinct mechanisms. A suppressor screen for mutants restoring Δ plzC migration identified downstream regulators, including CheX, a CheY-3 phosphatase. Genetic and phenotypic analyses revealed that PlzC promotes motility by modulating CheX, thereby influencing the frequency of direction changes during swimming. Notably, the role of PlzC in motility regulation is independent of CheZ, another CheY-3 phosphatase, demonstrating that among the two CheY-3 phosphatases, only CheX is under PlzC control. This distinction suggests that CheY-3-P levels are regulated by at least two separate signaling pathways, one of which operates through PlzC. Despite its function in motility, CheX is not required for PlzC-mediated biofilm regulation, indicating pathway specificity. PlzC regulates biofilm formation through a mechanism that involves c-di-GMP binding, separating it from its CheX-dependent motility regulation. Together, our findings establish PlzC as a central regulator linking CheX-mediated motility and c-di-GMP signaling, thereby impacting motility and biofilm formation in V. cholerae .